2000
DOI: 10.1177/147323000002800304
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of Fas and Fas Ligand on Human Colonic Intraepithelial T Lymphocytes

Abstract: The expression of Fas, a cell surface receptor directly responsible for triggering cell death by apoptosis, and its ligand (FasL) was investigated on both human colonic intraepithelial T lymphocytes (IELs) and peripheral blood mononuclear lymphocytes (PBMLs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Because of the persistent exposure to a diverse number of antigens encountered in the gastrointestinal tract, gut lamina propria T lymphocyte (T-LPL) numbers are controlled by induction of Fas-mediated apoptosis (12). T-LPL often express high levels of Fas (12,19); however, in cases of inflammatory bowel disease, Fas expression levels in T-LPL as well as T-LPL sensitivity to Fas-mediated apoptosis are often decreased (3,5,41,42). In the functional level, it was reported that mice with Fas deficiency in the colon tissues are hypersensitive to DSSinduced colitis (34), whereas mice lacking FasL exhibited more severe and persistent colitis than control WT mice (36).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the persistent exposure to a diverse number of antigens encountered in the gastrointestinal tract, gut lamina propria T lymphocyte (T-LPL) numbers are controlled by induction of Fas-mediated apoptosis (12). T-LPL often express high levels of Fas (12,19); however, in cases of inflammatory bowel disease, Fas expression levels in T-LPL as well as T-LPL sensitivity to Fas-mediated apoptosis are often decreased (3,5,41,42). In the functional level, it was reported that mice with Fas deficiency in the colon tissues are hypersensitive to DSSinduced colitis (34), whereas mice lacking FasL exhibited more severe and persistent colitis than control WT mice (36).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of both molecules has been demonstrated within other cell types, including the testicular Leydig cell, 22 natural killer cells, 23 and colonic intraepithelial T lymphocytes. 24 Fas/Fas ligand binding usually induces apoptosis within the Fas expressing cells. 25 This suggests that pancreatic islet cells must possess an additional mechanism for inhibiting "self-induced" Fas/ Fas ligand triggered apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…These lymphocyte populations are important for immunologic development, immunoglobulins, cytokines and growth factors production, epithelial cells proliferation and differentiation, and intestinal tolerance [16][17][18]. Thus, mucosal lymphocytes have a series of patterns recognition receptors that interact with bacterial molecular patterns, helping to modulate intestinal innate immunity and an appropriate adaptive immune response [19], also providing the most effective immune protection in a strictly regulated fashion, to preserve the integrity and the vital functions of the intestinal mucosal epithelium [20].…”
Section: Discussionmentioning
confidence: 99%